Business model innovation and third-party alliance on the survival of new firms. (January 2015) - Velu, Chander
Abstract: In this study, we address the question of how the degree of business model innovation affects the survival of new firms. We present a newly constructed data set of 129 new firms that launched electronic trading platforms in the US bond market between 1995 and 2004 following the advent of Internet technology. We analyze the founding and survival of these new firms during the period of our study. We find that new firms with a high or low degree of business model innovation are more likely to survive for longer than new firms with a moderate degree of business model innovation. We show that partnering with third-party firms with complementary assets reduces the survival of new firms as the degree of business model innovation increases. We discuss the implications of our findings for managers, policy-makers and researchers. Highlights: We present a study using data set of 129 new firms that launched electronic trading platforms in the US bond market. We analyze the founding and survival of these new firms during the period of our study. We find that new firms that have a high or low degree of business model innovation are more likely to survive longer. We find that partnering with third-party firms with complementary assets reduces the survival of new firms as degree of business model innovation increases.